Educação ambiental, intercultura e formação de professores(as): contribuições de Paulo Freire - Rosa, Cleni Inês da (2012)
This research of Master s Degree in Education in the Line of Formation, Knowledge and Professional Development in PPGE of the Federal University of Santa Maria has as its goal to contribute with theoretical and epistemological subsidies for the teachers formation, seeking to broaden the conceptions and practices in Environmental Education in the school routine in an intercultural perspective of Education. This dissertation has a bibliographic character that brings a study of some ideas and propositions of Paulo Freire that may contribute to the teachers formation regard the Environmental Education particularly. Searching for a bigger theoretical and bibliographical knowledge, intercultural dialogues were established (Fleuri, 2003), between the dialogues and readings performed about education, Environmental Education and Teachers Formation. Still, it contains the investigation of some propositions present in Freire s works that may contribute to the comprehension of environmental issues in a global perspective, such as citizenship, lovingness, tolerance, popular knowledge and autonomy. The reference that guided the investigative and reflexive look of the researcher (BARCELOS, 2005) in the sense of the production of research information (JACQUES GAUTHIER, 1998), was established after dialogues that privileged the intercultural aspects (CANCLINI, 2003) with imaginaries and representations of the environmental issues, the teachers formation, (ARROYO, 2004), Paulo Freire (1994, 1997, 2001, 2008), between many other authors. In that way my path has been built, seeking to understand how some propositions, from the Freurians assumptions can contribute to the teachers formation. The relevance of this research is in the perspective of an education that values the dialogue, the communication and the autonomy, because for Paulo Freire, it s by the education that you promote the individuals transformation. Transform in the sense of the student becoming the real subject of the construction of your knowledge.